Partisipasi Pembelajaran Bahasa Indonesia Kelas XI dalam Program Habit-Forming MAN 2 Samarinda - Rinda Cahya Mudiawati; Susilo Susilo; Mohammad Siddik (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2023)
The habit-forming program is designed by schools/madrasas to accustom learners to habituation. Indonesian language learning materials can participate in habit-forming programs. The purpose of this study is to describe the participation of Indonesian language learning in the habit-forming program in terms of Indonesian language learning materials. Researchers used descriptive naturalistic qualitative methods to describe what materials in Indonesian language learning can participate in the habit-forming program at MAN 2 Samarinda. The data sources and samples in this study were students in grade XI. Researchers used triangulation techniques to collect data while testing the credibility of different data from the same source. The data analysis technique of this research uses the model developed by Creswell, namely: (1) organizing and preparing data; (2) reading all data; (3) coding; (4) describing coding; (5) constructing data. The results of this study show that Indonesian language learning materials in class XI can participate in the habit-forming program. The stimulus-response of Indonesian language learning in the habit-forming program, among others: Indonesian language learning materials as a form of habituated stimulus; and the participation of Indonesian language learning materials in the habit-forming program as a form of habituated response.